Niebiali, niemężczyźni i inni nieprawdziwi obywatele. O reprodukcji społecznych nierówności w książce Karen Brodkin „How Jews Became White Folks and What That Says about Race in America” - Agnieszka Pasieka (Studia Litteraria et Historica, 2014)
Non-whites, non-males and other non-genuine citizens. The reproduction of social inequalities as seen in Karen Brodkin’s 'How Jews Became White Folks and What That Says about America'